PERANCANGAN TATA LETAK GUDANG PADA PT.X DI SURABAYA - Helmi Sofyan Sulisno; Fitri Novika Widjaja; Stefanus Budy Widjaja S. (CALYPTRA, 2020)
PT.X is A a construction company. The warehouse is 1500 m2 large. In the initial condition, the warehouse item has not been organized, the laying of products are still mixed and products have not been grouped. This causes the workers having difficulties to identifying the product and to pickup the products. There is damaged on packaging and product which need to be repair cause by imprecise material handling. Based on this problem, relayouting and choosing the right material handling needs to be done. In the new layout design has been determined the partition of storage areas as well as additional areas. There is an increase in warehouse capacity by 120 pallets from the previous 1129 pallets to 1249 pallets. Installation of label systems can be a solution in answering the issue of tracking goods. The use of unit load such as pallets and wooden crates is a solution to the efficient loading and unloading process and reduces manual handling that may be hazardous to workers.